Key topics in general surgery - Lattimer, C. R.; Wilson, N. M.; Lagattolla, N. R. F. (Oxford : BIOS Scientific, 2002)
this book explain the new topics in general surgery .
this book content abdominal trauma --aneurysms -- blood transfusion --chest trauma -- day case surgery -- endoscopy -- head injury -- intensive care -- pancreatic cancer -- screening -- the spleen -- trauma management -- varicose veins-- varicose veins.
Surgery. include index.
Includes bibliographical references and index.
All age.
Keywords: Surgery